Cenários portuenses de insegurança. Contributos do interaccionismo simbólico para uma análise da construção mediática do desvio - Paula Guerra (2002)
In this article we will study the social problems from the perspective that the study of the emergence of a social problem is one of the best developers of this work of 'construction of reality' to regain the title of a famous work of Sociology, because it condenses all aspects of this process. Specifically, we will give particular emphasis to the importance of the media construction of social problems, stressing that "to give a necessarily selective view and privileging certain interpretations of the event, the press helps to make sense of these political and social movements with meanings, while , overabundant and ambiguous. However, it would be too simple to see only the journalists as 'handlers' who manufacture, to your taste, the events when preparing biased reviews. They are themselves the subject of manipulation strategies by various social groups that organize demonstrations and look through them, to attract more or less success to the attention of journalists to have a chance of appearing in the media. This analysis option also allows us to discuss the current applicability of the symbolic interactionism, as it has been resumed with some prodding in the context of contemporary sociological research.